2023
DOI: 10.1097/ico.0000000000003418
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy of Perfluorohexyloctane Ophthalmic Solution for the Treatment of Patients With Dry Eye Disease: The KALAHARI Study

Eugene E. Protzko,
Bruce A. Segal,
Michael S. Korenfeld
et al.

Abstract: Purpose: The aim of this study was to assess the long-term safety and efficacy of perfluorohexyloctane (PFHO) ophthalmic drop (formerly NOV03) for treatment of dry eye disease (DED). Methods: KALAHARI was a phase 3, multicenter, single-arm, open-label extension study in patients aged 18 years or older with DED associated with Meibomian gland dysfunction who completed the randomized, double-masked, hypotonic saline-controlled GOBI study. Patients instill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Two Phase III clinical trials (GOBI [ClinicalTrials.gov identifier: NCT04139798] and MOJAVE [ClinicalTrials.gov identifier: NCT04567329]) have shown a consistent improvement of two primary endpoints (tCFS and dryness scores), demonstrating a safety profile similar to that of hypotonic saline solution [21,22]. The most recent phase III open-label extension study (KALAHARI [ClinicalTrials.gov identifier: NCT04140227]), revealed that improvement in both tCFS and dryness scores was maintained in the PFHO group and the drug was deemed safe [23]. Other studies further corroborate its efficacy in ameliorating DED symptoms with satisfactory tolerability and excellent patient satisfaction [24,25].…”
Section: Perfluorohexyloctane Ophthalmic Solution (Pfho)mentioning
confidence: 99%
“…Two Phase III clinical trials (GOBI [ClinicalTrials.gov identifier: NCT04139798] and MOJAVE [ClinicalTrials.gov identifier: NCT04567329]) have shown a consistent improvement of two primary endpoints (tCFS and dryness scores), demonstrating a safety profile similar to that of hypotonic saline solution [21,22]. The most recent phase III open-label extension study (KALAHARI [ClinicalTrials.gov identifier: NCT04140227]), revealed that improvement in both tCFS and dryness scores was maintained in the PFHO group and the drug was deemed safe [23]. Other studies further corroborate its efficacy in ameliorating DED symptoms with satisfactory tolerability and excellent patient satisfaction [24,25].…”
Section: Perfluorohexyloctane Ophthalmic Solution (Pfho)mentioning
confidence: 99%